A DT fusion reactor design in field-reversed configuration using normal conductive coils. (1st November 2017) - Hirano, Y.; Sekiguchi, J.; Matsumoto, T.; Asai, T.; Nogi, Y.; Watanabe, M.; Takahashi, T.
Abstract: Assuming continued stability, favorable energy confinement time scaling, and an effective current drive and maintenance methods, a feasible DT fusion reactor design is proposed for field-reversed configuration (FRC) which uses normal conductive copper magnetic field coils at room temperature. The reactor has 3 GW fusion power, 1.5 MW m −2 neutron wall loading at the first wall, and thermal loading less than 1 MW m −2 at diverter plates. Plasma has an almost straight cylindrical shape of 40 m in length and 8.6 m in diameter. FRC can obtain very high beta (over 0.7 in average) and the magnetic field strength of the reactor will be 1.215 T, which can be produced by normal conductive coils having 70 m in length, 17.6 m in diameter, and 1.5 m in thickness with 0.6 effective conductive area ratio. Its Ohmic power loss is 74 MW, which is less than 10% of the expected electric power output. A scenario to reach ignition from the initial formation is considered. At first, two FRCs are formed at the both ends of the reactor by fast theta-pinch with a negative bias magnetic field 6 m in length and 0.5 m in diameter. The FRCs are accelerated up to 250 km s −1 by the gradient of magnetic field strength towards the center of the burning region, collide with each other, and form a single large FRC. Their kinetic energy is converted to thermal energy, and the merged FRC is 10 m in length and 1.8 m in diameter. This FRC plasma is brought to ignition by intensive neutral beam injection (NBI) heating and particle supply. Given 200 s heating duration, the maximum NBI power is 250 MW before alpha particle heating becomes significant. After ignition, NBI heating is not required, but there is a possibility that some part of equilibrium current must be supplied by the NBI in the MeV region.